Memaknai Persaingan Usaha Yang Berkeadilan Dan Menyejahterakan Dalam Perspektif Keadilan Sosial - Al Kautsar, Izzy (Yurispruden: Jurnal Fakultas Hukum Universitas Islam Malang, 2024)
This paper intends to harmonize and analyze the conception of the idea of fair and prosperous business competition, attempt to find the essence of business competition based on social justice, and provide a theoretical contribution to the enforceability of business competition law, especially providing practical offers for the business competition supervisory commission. This research uses normative method with conceptual and statutory approaches. The results of the research show that the paradigm of fair and welfare business competition is seen in the nuances of harmonious and ideal competition to maintain the principles of competitive justice, efficiency, and welfare of all market components. The essence of social justice in competition lies in its goal to create a fair and balanced market system for all levels of society.